Graphical modeling of additive color mixing. Analyses of electromagnetic effects as colors of the vision analyzer - Ignatov, I.; Popova, T.P. (Medicni Perspektivi, 2024)
The human visual analyzer is a high form of evolution. Some jellyfish can distinguish light and dark objects with sensitive cells. Squids, octopuses, and nautiluses from Cephalopods family have eyes with which they can see objects. Visual information is processed in the brain. In fishes, the visual analyzer evolved. Fishes living below 100 m depth inhabit a world with blue light. The authors consider the evolution of vision in these fishes due to the lowest absorption of blue and violet colors of electromagnetic waves from the optical spectrum. Subsequently, on land, in humans vision evolved towards the green color. Green is the most prevalent color on the land. In humans, three light-sensitive cones evolved – S, M, and L. S cones are most sensitive to blue, M – to green, and L – to red color in the spectrum. Some humans retain sensitivity of S to genetic changes and disorders. Additive color mixing is a high form of color perception in humans. The additive mixing of different colors achieves a new color in the human visual analyzer. Remarkably, different individuals perceive observed images in varying manners. Mixing neighboring colors on the spectrum gives one, two, or three colors. This process is estimated using graphical modeling. The graphical modeling with two colors allows for the creation of additive colors. One, two, or three additive colors can be obtained. The production of colors results from the light sensitivity of S, M, and L cones. An analysis that physically demonstrates the mixing of green and red colors, resulting in the colors yellow or orange. When blue and red are mixed, the resulting colors are green, yellow, and orange is proposed. The additive mixing of blue and yellow gives green. The subjective nature of visual perception, influenced by the viewer’s heightened sensitivity to one of the colors, becomes evident in the presence of two colors. Notably, when the background is violet, the sensitivity of the blue cones diminishes.